2006
DOI: 10.1093/humrep/del254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dehydroepiandrosterone on oocyte and embryo yields, embryo grade and cell number in IVF

Abstract: This study confirms the previously reported beneficial effects of DHEA supplementation on ovarian function in women with diminished ovarian reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(161 citation statements)
references
References 42 publications
10
150
1
Order By: Relevance
“…Six trials including 163 patients that studied women older than 36 also indicated increased oocyte numbers after DHEA treatment (WMD 1.31, [13] Ca se-control None None N/A Intention to treat analysis *** * ** Barad [12] Prospective cohort study None None N/A Intention to treat analysis *** * ** Sonmezer [23] Prospective cohort study None None N/A Intention to treat analysis *** * ** Gleicher [32] Case-control None None N/A Intention to treat analysis *** * ** Wiser [14] RC T Artini [33] RC T Moawad [24] RCT Fusi [25] Prospective cohort study None None N/A Intention to treat analysis *** * ** Hyman [26] Prospective cohort study None None N/A Intention to treat analysis ** * ** Singh [27] Prospective cohort study None None N/A Intention to treat analysis ** * ** Yeung [32] RCT Yilmaz [36] Prospective cohort study None None N/A Intention to treat analysis *** * ** Jirge [15] Prospective cohort study None None N/A Intention to treat analysis *** * ** Kara [28] R C T Vlahos [2] Prospective cohort study None None N/A Intention to treat analysis **** * ** Xu [16] C a s e -control None None N/A Intention to treat analysis ** * ** Yeung [6] R C T Zangmo [17] Prospective cohort study None None N/A Intention to treat analysis ** * ** Zhang [29] RCT Tartagni [30] RCT Tsui [31] Prospective cohort study None None N/A Intention to treat analysis *** * ** Fig. 6b) [12,14,17,25,26,31]. We also compared the results from case-control trials.…”
Section: Oocyte Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…Six trials including 163 patients that studied women older than 36 also indicated increased oocyte numbers after DHEA treatment (WMD 1.31, [13] Ca se-control None None N/A Intention to treat analysis *** * ** Barad [12] Prospective cohort study None None N/A Intention to treat analysis *** * ** Sonmezer [23] Prospective cohort study None None N/A Intention to treat analysis *** * ** Gleicher [32] Case-control None None N/A Intention to treat analysis *** * ** Wiser [14] RC T Artini [33] RC T Moawad [24] RCT Fusi [25] Prospective cohort study None None N/A Intention to treat analysis *** * ** Hyman [26] Prospective cohort study None None N/A Intention to treat analysis ** * ** Singh [27] Prospective cohort study None None N/A Intention to treat analysis ** * ** Yeung [32] RCT Yilmaz [36] Prospective cohort study None None N/A Intention to treat analysis *** * ** Jirge [15] Prospective cohort study None None N/A Intention to treat analysis *** * ** Kara [28] R C T Vlahos [2] Prospective cohort study None None N/A Intention to treat analysis **** * ** Xu [16] C a s e -control None None N/A Intention to treat analysis ** * ** Yeung [6] R C T Zangmo [17] Prospective cohort study None None N/A Intention to treat analysis ** * ** Zhang [29] RCT Tartagni [30] RCT Tsui [31] Prospective cohort study None None N/A Intention to treat analysis *** * ** Fig. 6b) [12,14,17,25,26,31]. We also compared the results from case-control trials.…”
Section: Oocyte Numbersmentioning
confidence: 99%
“…DHEA can also enhance the level of follicular insulin-like growth factor-1 (IGF-1), which promotes folliculogenesis by enhancing the effect of gonadotropin and reducing follicular arrest [7][8][9]. Recently, treatment with DHEA has been shown to result in improved ovarian response in patients with POR [2, 6,[10][11][12][13][14][15][16][17]. An international survey showed that 26 % of IVF clinicians add DHEA as an adjuvant to IVF treatment protocols in such women [18].…”
Section: Introductionmentioning
confidence: 99%
“…They noted a significant increase in oocyte and embryo numbers, better embryo grades, and improved average embryo scores [20]. In a subsequent study by the same group, eighty nine patients with poor ovarian reserve were supplemented with DHEA for 4 months.…”
Section: Published Studiesmentioning
confidence: 92%
“…Successively, it has been proposed for a category of women such as those affected by premature ovarian failure (POF), premature ovarian aging (POA), diminished ovarian reserve (DOR) as defined by the Bologna criteria [5] and in women with increased stimulating hormone (FSH) [6]. Some authors reported increased number of oocytes retrieved and improved embryo quality [7,8], low aneuploidyrate [9], higher pregnancy rates [10] and increased spontaneous pregnancies in patients with POF (27 Mamas, 2009a) and high AMH levels [2,11], however no positive effect was found when women with normal ovarian reserve were treated with DHEA [12]. The beneficial effect of the use of DEA for women with DOR undergoing IVF has been mainly reported by retrospective studies, while results from recent meta-analyses and randomized control trials showed that DHEA pre-treatment did not improve clinical pregnancies.…”
Section: Dehydroepiandrosterone (Dhea)mentioning
confidence: 99%